Strengthening Global Diversity Character through Pancasila Education Learning at Makassar City State Senior High Schools - Adim Isral Ayubi; Firman Umar; Bakhtiar Bakhtiar (SEIKAT: Jurnal Ilmu Sosial, Politik dan Hukum, 2026)
This study aims to determine: (1) The relevance of the Pancasila Education learning program to the formation of global diversity character in Makassar City State Senior High Schools; (2) teacher strategies in strengthening global diversity character through Pancasila Education learning; and (3) factors that support and inhibit in strengthening global diversity character through Pancasila Education learning in Makassar City State Senior High Schools. This study uses a qualitative approach with a descriptive research type. This research was conducted at Makassar State Senior High School 1 and Makassar State Senior High School 4. Research informants included the principal, Pancasila Education teachers, and students. The types of data used in this study were primary data and secondary data. Data collection techniques were interviews, observation, and documentation. Data validity testing used source triangulation, technical triangulation, and time triangulation. Data analysis techniques used the Miles and Huberman model which included data reduction, data presentation, as well as drawing conclusions and verification. The results of this study indicate that (1) The Pancasila Education learning program has a very strong relevance to the formation of global diversity character which includes aspects of knowing and appreciating culture, the ability to communicate interculturally and interact with others, as well as reflection and responsibility for diversity experiences. (2) Teacher strategies in strengthening global diversity character through Pancasila Education learning are integrated through learning planning and implementation. (3) Factors that support the strengthening of global diversity character through Pancasila Education learning include school support, facilities and infrastructure, and the diversity of student backgrounds. The factors that inhibit the strengthening of global diversity character through Pancasila Education learning include students' lack of understanding of the concept of global diversity, the influence of social media, and parenting patterns from the family environment.